ISOLASI BAKTERI PENGHASIL ENZIM PROTEASE BACILLUS AMYLOLIQUEFACIENS IROD2 PADA ONCOM MERAH PASCA FERMENTASI 48 JAM - Dwi Pamaya; Sakti Imam Muchlissin; Endang Tri Wahyuni Maharani; Sri Darmawati; Stalis Norma Ethica (Universitas Muhammadiyah Semarang, 2018)
Proteolytic bacteria are the bacteria capable of producing extracellular protease enzymes, namely protein-breaking enzymes that are widely used in many industrial fields. This study aimed to isolate a proteolytic bacterium found on 48-h post-fermented oncom and molecular identification method. The initial isolation and purification process of the colony was carried out using Nutrient Agar medium. Selection of protease enzyme obtained by bacterial isolate was done on Milk Skim Agar medium. Identification process of the isolate was done through amplification of 16S rRNA gene using PCR, sequencing and analysis of gene sequences using BLAST program. From the isolation process a bacterial isolate that has proteolytic by the ability to produce a clear zone of 82.00 on plate. The result of the 16S rRNA gene sequence analysis showed that the proteolytic bacterial isolate obtained in this study had a 98% homology level with 16S ribosomal RNA isolate of Bacillus amyloliquefaciens strain A1142 (Genbank access code: KTT722836.1). Based on the results of the molecular identification, the isolate was identified as Bacillus amyloliquefaciens strain IROD2 (IROD2 = Indonesia Red Oncom Day2). As conclusion, from 48-h post fermented red oncom, a protease producing bacterial strain molecularly identified as Bacillus amyloliquefaciens strain IROD2. Keywords: Moleculary was identified, Proteolitic bacteria, 16S rRNA gene